1998
DOI: 10.1177/002215549804600103
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-fracture Cytochemistry: A New Method Combining Immunocytochemistry and Enzyme Cytochemistry on Replicas

Abstract: We describe a new freeze-fracture cytochemical technique consisting of combined immunocytochemistry and enzyme cytochemistry. This technique reveals the relationship between molecules in biological membranes by double labeling with two different cytochemical markers (i.e., immunogold probes and cerium). In this method, antigens were detected with specific primary antibodies and appropriate secondary immunoprobes. Subsequently, alkaline phosphates activity was detected with cerium as the capture agent on the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In contrast, the octyl-glucoside, previously reported to be efficient for eukaryotic cells (Takizawa et al 1998;Takizawa 1999), showed nonspecific labeling and insufficient digestion of the replicas ( Figure 2D). …”
Section: Efficacy Of Different Detergentsmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, the octyl-glucoside, previously reported to be efficient for eukaryotic cells (Takizawa et al 1998;Takizawa 1999), showed nonspecific labeling and insufficient digestion of the replicas ( Figure 2D). …”
Section: Efficacy Of Different Detergentsmentioning
confidence: 70%
“…In a further effort to evaluate the usefulness of the SDS-FRL method on H. pylori , we tested a variety of detergents, some previously reported to be useful on eukaryotic cells, e.g., octyl-glucoside (Takizawa et al 1998). In the test series with different detergents, there were cases with unfractured cell components, which were incompletely digested and remained attached to immunolabeled replicas, marked in the micrographs with an asterisk (*).…”
Section: Efficacy Of Different Detergentsmentioning
confidence: 99%
“…The replicas are cleaned from cellular components by detergent digestion (Fujimoto 1995(Fujimoto , 1997Takizawa and Robinson 2000), whereas biomolecules that are in direct contact with the replica Wlm like membrane lipids and membrane bound proteins keep bound to the replica. After removing the detergent by several buVer washings the replica-bound membrane molecules can be labeled with probes for immuno cytochemistry or enzyme cytochemistry (Takizawa et al 1998). For this technique the use of chemically unWxed cells is essential because in aldehyde Wxed cells the cellular components are cross-linked, therefore they are not readily dissolvable by detergents.…”
Section: Introductionmentioning
confidence: 99%
“…To conceptualize this, one explanation might be that the fixative makes the metal replica non-electrostatic or reduces replica hydrophobicity, even though the predominant part of the fixed biological material has been dissolved by the detergent-treatment and washed off. Still, previous reports have established that both phospholipids and proteins remain in sufficient quantity for immunolabeling Takizawa et al, 1998).…”
mentioning
confidence: 99%